«Tú no eres quien yo espero»: colonización, resistencia y género en las islas Marianas (siglos xvi-xix) - Alexandre Coello de la Rosa; Luis J. Abejez (Mélanges de la Casa de Velázquez)
Compared with the image of apparent inaction and passivity of the Chamorro women, more typical of the sexualized model of the natives of the Pacific than of reality, this article shows the other side of the coin that filters through the Spanish official documents, but also those of European travellers and sailors, that reveals a situation in which the native women put into practice different strategies, adaptive and of resistance, that turned them into protagonists of their own lives. This attitude went so far as to cross the limits of their own ethnic group to permeate the whole of the Chamorro women living in the island of Guåhån.